Auricular reconstruction using Medpor combined with different hearing rehabilitation approaches for microtia. (1st June 2021) - Jiang, Chenyan; Zhao, Chen; Chen, Bin; Lu, Lixin; Sun, Yuxin; Yan, Xiaojun; Yi, Bin; Wu, Hao; Shi, Runjie
Abstract: Background: Congenital microtia-atresia affects patients in two specific ways: severe conductive hearing loss and difficulty in integrating into social environments due to auricle malformation. Aims/objectives: To investigate the safety and efficacy of single-stage auricular reconstruction and hearing rehabilitation in children with microtia and external auditory canal atresia. Material and methods: From January 2016 to December 2019, we included 32 patients with microtia and external canal atresia who received auricle reconstruction with high-density polyethylene (Medpor) framework and three different hearing rehabilitation approaches at the Ninth People's Hospital affiliated to Shanghai Jiao Tong University School of Medicine. Twenty patients underwent the traditional external auditory canal and middle ear repair (EACR), eight patients were implanted with Bonebridge (BB) devices, and four patients were implanted with bone-anchored hearing aid (BAHA) in one stage. Postoperative changes in auricle morphology and hearing and speech recognition and occurrence of complications were evaluated. Results: After 6–24 months of follow-up, the auricle shape recovered well in all three groups, and the average score of 14 fine structures in the auricle was 9.43 (EACR), 10.67 (BB), and 9.75 (BAHA) points. The average score of auricle symmetry was 6.83 (EACR), 6.00 (BB), and 6.44 (BAHA) points. No significant differences in auricle shape were observed among the three groups ( p > .05). After surgery, the average hearing improvement in the BB group was 43.33 dB, and the average speech recognition threshold declined to 42.28 dB. In the BAHA group, the average hearing improvement was 35 dB, and the average speech recognition threshold declined to 33.5 dB, similar to that of the BB group. However, in the EACR group, the average hearing improvement was only 4.13 dB, and the average speech recognition threshold declined to 11.36 dB. No vertigo, tinnitus, cerebrospinal fluid leakage, facial nerve paralysis, osseointegration failure, and other complications occurred in all the patients. In the EACR group, auricle stent fracture, ear canal restenosis, and canal atresia occurred in one patient each. In the BAHA group, two patients developed local ear infections. Conclusions and significance: The procedure of single-stage auricular reconstruction and hearing rehabilitation for microtia is feasible and effective. The appropriate method of hearing reconstruction should be determined by evaluating the development of the inner and middle ear of the patients. For those patients with poor development of the mastoid and ossicular chain, hearing aid devices are recommended to achieve a stable and significant hearing effect.